ONTOLOGI PENDIDIKAN HUMANIS DAN RELEVANSINYA DENGAN PENDIDIKAN DI ERA GLOBAL - Anwar Sa'dullah (VICRATINA, 2019)
AbstractEducation essentially humanizes humans, a variety of cases that arise one of which violence in education or resistance to teachers reflects the failure of the educational process. Humanist education becomes an important study to be elaborated on the background and purpose of the concept. Given the global conditions provide opportunities for every human being to carry out a variety of activities without restrictions. So if you don't have the knowledge to manage it, you will fall into error. Keywords: Ontology, Humanist Education, Global Abstract Pendidikan hakikatnya memanusiakan manusia, berbagai macam kasus yang muncul salah satunya kekerasan dalam pendidikan atau perlawanan terhadap guru mencerminkan kegagalan proses pendidikan. pendidikan humanis menjadi kajian penting untuk diuraikan tentang latar belakang dan tujuan konsep tersebut. Mengingat kondisi global memberikan kesempatan pada setiap manusia untuk melakukan berbagai macam aktivitas tanpa batasan. Sehingga jika tidak memiliki ilmu untuk mengelolanya, akan terjerumus pada kesesatan. Keywords : Ontologi, Pendidikan Humanis, Global